Characteristics of re-gripping techniques preceding scored throws in international-level judo competition - Ito, K.; Hirose, N.; Maekawa, N. (Central European Journal of Sport Sciences and Medicine, 2019)
Significant changes in kumite tactics were verified after the 2013 International Judo Federation rule revision, which mandated that competitors initiate sparring immediately at match outset. The research contained in this paper focused on the re-gripping techniques which were affected by this rule revision, relating to the gripping targets, the use of cross gripping techniques, body rotation when executing throws, and the attacking patterns. In total, 372 men`s contests from the Judo Grand Slam Paris 2016 were analyzed using All Japan Judo Federation Science and Research Department SMART Edge system. Throws resulting in scores were identified and the preceding kumite tactics were analyzed. Re-gripping techniques resulted in significantly higher score rates than the no re-gripping techniques when competitors grabbed the place of the competition number, and the place(s) other than the collar and sleeve with at least one hand except the place of the competition number. Re-gripping the opponent and targeting the place of the competition number might facilitate scoring. Using the re-gripping techniques could make a variety of gripping targets effective to score. We emphasize the importance of classifying kumite techniques into two major patterns: re-gripping and no re-gripping techniques when coaching competitors for kumite tactics.